4X+(X+6)=-15-2X

Simple and best practice solution for 4X+(X+6)=-15-2X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4X+(X+6)=-15-2X equation:


Simplifying
4X + (X + 6) = -15 + -2X

Reorder the terms:
4X + (6 + X) = -15 + -2X

Remove parenthesis around (6 + X)
4X + 6 + X = -15 + -2X

Reorder the terms:
6 + 4X + X = -15 + -2X

Combine like terms: 4X + X = 5X
6 + 5X = -15 + -2X

Solving
6 + 5X = -15 + -2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '2X' to each side of the equation.
6 + 5X + 2X = -15 + -2X + 2X

Combine like terms: 5X + 2X = 7X
6 + 7X = -15 + -2X + 2X

Combine like terms: -2X + 2X = 0
6 + 7X = -15 + 0
6 + 7X = -15

Add '-6' to each side of the equation.
6 + -6 + 7X = -15 + -6

Combine like terms: 6 + -6 = 0
0 + 7X = -15 + -6
7X = -15 + -6

Combine like terms: -15 + -6 = -21
7X = -21

Divide each side by '7'.
X = -3

Simplifying
X = -3

See similar equations:

| f(x)=x^2+10x+3 | | t/3-t-5/2=6 | | f(x)=x^2+10x-1 | | x/3-2(x-7)/5=4/3x | | (t/2)-(t-5)/2=6 | | x/3-2x-14/5=4/3x | | (2-6i)/(4+7i) | | -4v^2+19v-31=0 | | 4-23a=18 | | 4x^6-14x^4/2x^3 | | 6y^2-11y+8=0 | | a^2+6a+5= | | -8x+5y=-17 | | x/2+8=2x+13/2 | | 9x^4-42x^3+64x^2-32x=0 | | -2x+y=3/5 | | 50n=118/100 | | 45/n=61/100 | | 25/n=12/100 | | 64x^2-32x=0 | | 41/n=5/100 | | 99/n=99/100 | | 1024x=x-252 | | y=8/7x | | 2w^2+8w+31=(w+6)(w+6) | | 17=5+5+2x-3 | | 0=a^2-9a+12 | | 9a-a^2=12 | | y-22=-1.3333(x-6) | | 2(2b+1)-6b= | | a=(3.14)(16) | | -y^4-2y=0 |

Equations solver categories